Assessment and evaluation at University: reflections from the past and future perspectives - Felisatti, Ettore (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
The impact of assessment and evaluation is relevant in the academic context. It helps to define quality standards, leading to changes in systems, processes and results. In this frame, assessment and evaluation strengthen and widen the methodological aspects and develop an interactive function that highlights the value of a dialogue between the actors involved, fostering integration and continuity between processes and their assessment. The article analyses some aspects related to the evolution of assessment and evaluation at university and focuses on the collegial involvement of a plurality of actors in the assessment and dynamics. In particular, in the need of widening participation of stakeholders contributing to assessment processes, we value the direct and indirect contribution of students in the assessment practices to improving the quality of the education system and teaching. Three aspects, although non-exhaustive, within the complex scenario of assessment at university, are discussed: assessment as a contribution to the quality of teaching; assessment for learning; assessment of learning outcomes. For each aspect, an emblematic experience is presented highlighting how the role of students in assessment is developed as a key and diversified aspect.